Research Methods and Management. (15th February 2023) - Croucher, Richard
Abstract: This editorial introduces a virtual special issue containing a selection of innovative and highly cited papers on methodological questions recently published in the British Journal of Management . In an initial context section, it is argued that, while management research has drawn on methods from the core social sciences, it has cast its net wider to adopt methods from subjects and fields on the edge of the social sciences as they are normally conceived. These have also been important. It has, in turn, made significant methodological contributions both to those subjects and fields and, indeed, more widely. The contributions of the papers selected for inclusion in the special issue are delineated within this broad context.